Derivative Operators on Quantum (3) space with Two Parameters and Weyl algebra (European Journal of Pure and Applied Mathematics, 2012)
In this paper, we introduced a quantum space generated by three noncommutative coordinates with two commutation parameters. We also give Hopf algebra structure in order to construct bicovariant differential calculus over this quantum space. Morever, it is shown that noncommutative derivative operators corresponding the coordinates comprise Weyl algebra.